DIGITAL MEDIA CONVERGENCE OF BROADCAST RADIO - Nurcahyadi, Asep; Regina, Revi; Suardi, Safarina Bunga; Imawan, Khaerudin; Erawati, Dedet (Journal Of Social Science (JoSS), 2024)
The existence of media convergence is an effort to adapt radio to the digital era. Although many people think that radio will no longer survive in the midst of technological and information developments, in fact, many radios still survive and have loyal listeners and partnerships to use radio advertising services. This form of research aims to find out the application of media convergence carried out by Shelter 95.6 FM Radio's public relations to maintain its existence amid the presence of various new media as competitors and the development of technology and information. This research uses qualitative research methods and data collection by interviewing 2 sources with public relations and broadcasters and descriptive observations and data collection techniques through previous literature studies, strengthened by the Media Convergence theory developed by Henry Jenkins through the 3C approach (computing, communication & content). Some of the applications made by Shelter FM to compete with other media are the application of computing convergence media Shelter FM has adapted by broadcasting Shelter FM outside with only a laptop, microphone, and audio mixer and the application of communication convergence media live radio broadcasts and also streaming Shelter FM radio in the Shelter FM application and content convergence media by delivering information and broadcasting using digital technology, namely social media to expand networks and audiences.